Development of Flood Drain Direction using Mobile GIS and Spatial Interpolation Techniques in Municipality of Khon Kaen, Thailand - Pawattana, Chalermchai; Jeefoo, Phaisarn (Naresuan University Journal: Science and Technology (NUJST); Vol 30 No 3 (2022): July-September 2022DO - 10.14456/nujst.2022.22, 2021)
In this paper, techniques for interpolation of spatial elevation from elevation data by using mobile GIS field survey for flood drain direction mapping have been developed which can be served as a guideline for remote sensing and GIS operations to improve the efficiency of flood disaster monitoring and management in the municipality of Khon Kaen, Thailand. In order to estimate the interpolation of spatial elevation for flood direction, five GIS data were used such as satellite imagery, hydrology, road, boundary and elevation. The paper presents the flood drain direction mapping by using DEM data from IDW interpolation technique. The result was shown the flood water direction from Nong Khot lake and flow to Bueng Kaen Nakhon lake and the last flow to Bueng Thung Sang lake, respectively. Keywords: Mobile GIS, Inverse distance weight, Ordinary Kriging, Flood drain direction, Municipality of Khon Kaen